Design and Synthesis of Pro-Apoptotic Compounds Inspired by Diatom Oxylipins - Giovanna Romano; Emiliano Manzo; Gian Luigi Russo; Giuliana d'Ippolito; Adele Cutignano; Maria Russo; Angelo Fontana (Marine Drugs, 2013)
Oxylipins are a large and diverse family of fatty acid derivatives exhibiting different levels of oxidation of the carbon chain. They are involved in many biological functions in mammals, plants and diatoms. In this last group of organisms, they are suggested to play a role in the reproductive failure of copepod predators, showing clear pro-apoptotic effects on newborn nauplii. In this work, these compounds were tested for the ability to induce mitotic arrest in sea urchin embryos. We show for the first time that oxylipins have an increased efficacy in their corresponding methylated form. Natural oxylipins were also used as an inspiration for the rational design and synthesis of stable chemical analogs with apoptotic activity against tumor cell lines. This approach led to the synthesis of the linear C15-ketol (22) that was shown to induce apoptosis in human leukemia U-937 cells. These results are proof of the concept of the use of eco-physiological considerations as a platform to guide the search for novel drug candidates.